Pregunta
upstudy study bank question image url

\( \frac{x^{2}+5 x}{2}+\frac{12}{x^{2}+5 x}=-5 \) let \( x^{2}+5 x=a \)

Ask by Mathis King. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solutions are \( x=-4, -3, -2, -1 \).

Solución

Solve the equation \( \frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5\) - step1: Find the domain: \(\frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5,x \in \left(-\infty,-5\right)\cup \left(-5,0\right)\cup \left(0,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}\right)\times 2\left(x^{2}+5x\right)=-5\times 2\left(x^{2}+5x\right)\) - step3: Simplify the equation: \(x^{4}+10x^{3}+25x^{2}+24=-10x^{2}-50x\) - step4: Move the expression to the left side: \(x^{4}+10x^{3}+25x^{2}+24-\left(-10x^{2}-50x\right)=0\) - step5: Calculate: \(x^{4}+10x^{3}+35x^{2}+24+50x=0\) - step6: Factor the expression: \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x+1=0\\&x+2=0\\&x+3=0\\&x+4=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=-1\\&x=-2\\&x=-3\\&x=-4\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&x=-1\\&x=-2\\&x=-3\\&x=-4\end{align},x \in \left(-\infty,-5\right)\cup \left(-5,0\right)\cup \left(0,+\infty\right)\) - step10: Find the intersection: \(\begin{align}&x=-1\\&x=-2\\&x=-3\\&x=-4\end{align}\) - step11: Rewrite: \(x_{1}=-4,x_{2}=-3,x_{3}=-2,x_{4}=-1\) The solutions to the equation \( \frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5 \) are \( x=-4, -3, -2, -1 \).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To simplify things, let's substitute \( a = x^{2} + 5x \). The equation then becomes \( \frac{a}{2} + \frac{12}{a} = -5 \). Multiplying the entire equation by \( 2a \) (to eliminate the fractions) yields \( a^2 + 24 = -10a \). Rearranging gives us a quadratic equation: \( a^2 + 10a + 24 = 0 \). Now you can use the quadratic formula \( a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) to find values for \( a \). Next, once you've found the values for \( a \), substitute back to \( x^{2} + 5x \) in order to find the corresponding \( x \) values. Don’t forget to check for possible extraneous solutions resulting from our manipulations!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad